2023
DOI: 10.1097/rti.0000000000000728
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Features of Idiopathic Interstitial Lung Diseases

Kiran Batra,
Traci N. Adams

Abstract: Idiopathic interstitial pneumonias (IIPs) are a group of diffuse parenchymal lung diseases of unclear etiology and are distinguished from diffuse parenchymal lung diseases of known cause, such as connective tissue disease–related interstitial lung diseases or hypersensitivity pneumonitis by history, physical exam, imaging, serologic testing, and, when necessary, histopathology. The 2013 American Thoracic Society (ATS)/European Respiratory Society (ERS) guidelines are the most widely accepted classification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…A number of retrospective studies have shown that positron emission tomography cannot sufficiently differentiate between inflammation and malignancy, rendering resection to be the only definitive diagnostic method for this type of pathology ( 24 , 25 ). With the advancement of histopathologic and transbronchial biopsy techniques, it is now possible to diagnose DIP effectively while minimizing patient harm compared to open biopsy, open-chest biopsy has been gradually replaced ( 26 ). In addition, the TBLB technique used in the present case has markedly reduced the postoperative recovery time of patients, whilst accurately diagnosing their disease ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of retrospective studies have shown that positron emission tomography cannot sufficiently differentiate between inflammation and malignancy, rendering resection to be the only definitive diagnostic method for this type of pathology ( 24 , 25 ). With the advancement of histopathologic and transbronchial biopsy techniques, it is now possible to diagnose DIP effectively while minimizing patient harm compared to open biopsy, open-chest biopsy has been gradually replaced ( 26 ). In addition, the TBLB technique used in the present case has markedly reduced the postoperative recovery time of patients, whilst accurately diagnosing their disease ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the above disease's automatic diagnosis, there are few studies on the automatic diagnosis of honeycomb lung CT images, especially the identification of different grades of diseases. In fact, accurate grading of honeycomb lung can be achieved by considering its location, size, and texture characteristics [42]. Inspired by this, in this paper, we will pay attention to the automatic grading of honeycomb lung CT images to evaluate the severity of the disease.…”
Section: Grading Diagnosismentioning
confidence: 99%
“…Although there is a shared attribute with ILDs where lung volumes are reduced without airflow obstruction, small airways play a role in lung remodeling in the NSIP pattern. Most ILDs result in structural changes in small airways [70] and alveoli. Additionally, HP can cause inflammation to the bronchioles, leading to bronchial obstruction.…”
Section: The Small Airway Disease In Other Fibrotic Diseasesmentioning
confidence: 99%